Pauline concept of ministry in 2 Corinthians 4:1–15 and the religious celebrity syndrome in Nigeria - Enobong, Solomon I.; Ituma, Ezichi A.; Uroko, Favour C. (Hervormde teologiese studies, 2024)
This study aims to investigate the Pauline concept of ministry as delineated in 2 Corinthians 4:1–15 and its correlation with the prevalence of the religious celebrity syndrome within the Nigerian Church, with the objective of offering insights into addressing this phenomenon. In contemporary Nigerian Christianity, there has been a noticeable emergence of religious celebrities in Christian ministry who prioritise personal fame, material gain and sensationalism over the sincere and honest proclamation of the gospel of Jesus Christ. This trend raises concerns about the deviation from the biblical model of ministry, as exemplified by the apostle Paul, and its implications for the spiritual health of the church and its impact on society. Through a critical exegesis of 2 Corinthians 4:1–15, this study delves into Paul’s understanding of ministry, focussing on themes such as integrity, humility, suffering, selfless sacrifice and the exaltation of Christ. Additionally, qualitative research methods, including interviews, surveys and case studies, were employed to examine the extent and effects of religious celebrity syndrome in the Nigerian Church. The analysis of 2 Corinthians 4:1–15 underscores Paul’s emphasis on the sacrificial nature of Christian ministry, wherein servants of God are called to embody humility and prioritise the proclamation of the gospel above personal gain or acclaim. Concurrently, the qualitative research reveals the pervasive influence of the religious celebrity syndrome in the Nigerian Church, leading to spiritual shallowness, moral compromise and a distorted view of Christianity and Christian ministry in particular within the church and the larger society. Based on the findings, it is recommended that the Nigerian Church reaffirm its commitment to the Pauline model of ministry by promoting humility, integrity and a Christ-centred focus among its leaders and congregants.Contribution: This study highlights the importance of aligning contemporary ministry practices in the Nigerian Church with the principles elucidated by Paul in 2 Corinthians 4:1–15. By embracing humility, integrity and a fervent devotion to Christ, the Church can effectively combat the religious celebrity syndrome within its fold and reclaim its role as a catalyst for societal change.